Selling Out: The Inauthenticity Discount in the Craft Beer Industry - Frake, Justin (Management Science, 2017)
This paper investigates why audiences devalue organizations that behave inauthentically. One explanation is that inauthenticity leads to lower perceptions of product quality. This stems from the audience’s doubt of an inauthentic actor’s capability and commitment to produce high-quality goods. Another explanation is that audiences discount the symbolic value—or what the object represents—of products from inauthentic organizations. I empirically test each of these mechanisms in the craft beer industry. First, I exploit exogenous variation in consumers’ knowledge of craft brewers’ inauthentic identity (whether they are owned by a corporate brewer) to empirically demonstrate an inauthenticity discount. Next, I decompose audience evaluations to show that knowledge of a producer’s inauthenticity does not have a statistically significant impact on evaluators’ sensory experience of the product—its taste, smell, appearance, or mouthfeel—but that it does affect audience evaluations of the product’s symbolic value. This paper was accepted by Olav Sorenson, organizations.